Shaking-B misexpression increases the formation of gap junctions but not chemical synapses between auditory sensory neurons and the giant fiber of Drosophila melanogaster - Jezzini, Sami H. (PLoS One, 2018)
The synapse between auditory Johnston’s Organ neurons (JONs) and the giant fiber (GF) of Drosophila is structurally mixed, being composed of cholinergic chemical synapses and Neurobiotin- (NB) permeable gap junctions, which consist of the innexin Shaking-B (ShakB). Previous observations showed that misexpression of one ShakB isoform, ShakB(N+16), in a subset of JONs that do not normally form gap junctions results in their de novo dye coupling to the GF. Misexpression of the transcription factor Engrailed (En) in these neurons also has this effect, and in addition causes the formation of new chemical synapses. These results, along with earlier studies suggesting that gap junctions are required for the development of some chemical synapses, led to the hypothesis that ShakB would, like En, have an instructive effect on the distribution of mixed chemical/electrical contacts. To test this, we first confirmed quantitatively that ShakB(N+16) misexpression increased the dye-coupling of JONs with the GF, indicating the formation of ectopic gap junctions. Conversely, expression of the ‘incorrect’ isoform, ShakB(N), abolished dye coupling. Immunocytochemistry of the ShakB protein showed that ShakB(N+16) increased gap junctional plaques in JON axons but ShakB(N) did not. To test our hypothesis, fluorescently-labeled presynaptic active zone protein (Brp) was expressed in JONs and the changes in its distribution on the GF dendrites was assayed with confocal microscopy in animals with misexpression of ShakB(N+16), ShakB(N) or, as a positive control, En. Using different methods of image analysis, we confirmed our previous result that En misexpression increased the chemical synapses with the GF and the amount of GF medial dendrite branching. However, contrary to our hypothesis, misexpression of ShakB did not increase these parameters. Immunostaining showed no association between presynaptic active zones and the new ShakB plaques, further evidence against the hypothesis. We conclude that both subsets of JON form chemical synapses onto the GF dendrites but only one population forms gap junctions, comprised of ShakB(N+16). Misexpression of this isoform in all JONs does not instruct the formation of new mixed chemical/electrical synapses, but results in the insertion of new gap junctions, presumably at the sites of existing chemical synaptic contacts with the GF.